PEMETAAN KINERJA PUBLIC RELATIONS PERGURUAN TINGGI SWASTA MELALUI MEDIA SOSIAL DI MASA PANDEMI COVID-19 - Riza Hernawati; Maya Amalia Oesman Palapah; Tri Nur Aini Noviar (Unisba Press, 2022)
Public relations practitioners from private universities have a strategic role in formulating and implementing creative and innovative communication programs through the use of technology and new media, especially in the time of the Covid-19 pandemic like today. This study aims to map the performance of private-public relations practitioners in optimizing the role of social media to overcome problems that arise due to the pandemic, such as the absence of direct promotion and communication to prospective students and the decline in interest in high school/vocational equivalent graduates to continue to higher education, by using the method of qualitative case study approach. Data collection techniques are carried out through FGD, in-depth interviews, observations of Unisba-assisted private universities in Bandung, and literature review. The results of the study show that in responding to the application of communication technology during the pandemic, it is necessary to implement strategic steps, including the building of a special team, empowering the entire academic community and students as well, coordinating with related parties, and evaluating the use of social media as a means of promotion. The results of this study contribute to universities that want to design promotional activities through social media.